Microshear Bond Strength and Microleakage of a Restorative Composite Resin with Salivary Contamination at Different Time Intervals - rasoul sahebalam; Yeganeh Arian; alireza boruziniat; Abdolrasoul Rangrazi (Mashhad University of Medical Sciences, 2021)
Introduction : Saliva contamination is an inevitable and common challenge in the field of restorative dentistry. Recognizing and considering the key time of isolation is an effective strategy to prevent the deleterious effects of salivary contamination. The purpose of this study was to evaluate the effect of salivary contamination in the course of light curing on microshear bond strength and microleakage of a restorative composite resin. Methods: 140 human third molars were divided into seven groups each containing 10 samples for measuring the microleakage and the microshear bond strength. The specimen of each group was contaminated with human saliva at a certain time, while group1 was contaminated in prior to light curing. The samples in groups 2 to 7 were contaminated with saliva at 2, 5, 10, 15, and 20 s after the start of light curing, respectively. The specimens of group7 were light cured and contaminated afterwards with human saliva. Results: According to the gathered results, the time of saliva contamination had significant negative effects on the microshear bond strength to the dentin and enamel in the course of light curing throughout the first 2s and 5s, respectively. It was indicated by the microleacage test that the saliva contamination in the first 2s, 5s, and 10s during light curing had a higher microleakage than the other times. Conclusion: In conclusion, during light curing of the composite resin, the first 10s was high sensitive to saliva contamination and therefore the isolation is very important in this time.